Development of release methods for captive‐bred freshwater pearl mussels (Margaritifera margaritifera. Issue 2 (16th November 2016) - Kyle, Rebecca; Reid, Neil; O'Connor, Nessa; Roberts, Dai
Abstract: Biodiversity loss is a global problem with freshwater bivalves considered among the most endangered biota. The freshwater pearl mussel, Margaritifera margaritifera, is declining throughout its range owing to habitat degradation and overexploitation. In most of its range, populations are regarded as reproductively non‐functional, which has led to the development of captive breeding programmes. A novel method of releasing M. margaritifera was tested, with captive‐bred juveniles being released into the rivers caged in 'mussel silos' (protective concrete domes with ventilation creating upwelling to ensure water through‐flow). In total, 240 juvenile mussels were released and survival and growth rates were monitored for 18 months after release for three size classes: A (13.01–20.00 mm); B (10.01–13.00 mm); and C (4.01–10.00 mm). Two experimental treatments were tested: one in which sediment was added to each silo (allowing mussels to orientate and burrow) and one without sediment. Survival by the end of the experiment at month 18 was significantly higher for the largest size class at 97% (although growth was lowest in this cohort), and lowest for the smallest size class, at 61% (although growth was highest in this cohort). Survival and growth were unaffected by the experimental treatment suggesting that adding sediment offered no advantage. Growth was positively correlated both with water temperature and with particle size of suspended solids (both of which were collinear, peaking in summer). There are many ex situ breeding programmes for freshwater pearl mussels throughout Europe and the results of this study suggest that the use of mussel silos may be a useful tool to protect juvenile mussels, allowing them to be released at a relatively early stage of development and minimizing the risk of domestication. Copyright © 2016 John Wiley & Sons, Ltd.